Sensitivity analysis of safety performance of Indian construction organizations / S.V.S. Raja Prasad - Raja Prasad, S.V.S (Universiti Teknologi MARA , Shah Alam: Faculty of Architecture, Planning and Surveying, 2018)
Rapid growth of construction activity coupled with utilization of versatile construction equipment has resulted in complex occupational health and safety issues in Indian construction sector. The construction scenario in India is more complicated and governs to exposure to various hazards compared to other industries and it is essential to execute valid approaches of hazard control measures for improving safety performance of construction organizations. The main purpose of the study is to develop suitable construct to benchmark the safety performance in Indian construction organizations. Data envelopment analysis (DEA), being a robust tool, has been employed to evaluate the performance of industries. DEA, basically, takes into account the input and output components of a decision making unit (DMU), to calculate technical efficiency (TE). TE is treated as an indicator for safety performance of DMUs and comparison has been made among them. Fifty Indian construction organizations under ten construction segments including both real estate and infrastructure categories are chosen for comparison purpose. The analysis was conducted by considering two cases; with and without first aid cases in the total number of accidents. Data envelopment analysis was adopted under constant return scale model. The mean efficiency scores of basic and special case are 0.63, 0.75 and 0.77, 0.83 respectively. It is observed that all the efficient organizations are from infrastructure segment only. It has been observed that safety performance of construction organizations under real estate sector is consistently low as compared to infrastructure sector. The number of first aid cases in total number of accidents is influencing the technical efficiency scores of construction organizations.